2020
DOI: 10.1186/s13550-020-00713-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain SPECT perfusion and PET metabolism as discordant biomarkers in major depressive disorder

Abstract: Background Brain SPECT perfusion and PET metabolism have been, most often interchangeably, proposed to study the underlying pathological process in major depressive disorder (MDD). The objective of this study was to specify similarities and inconsistencies between these two biomarkers according to global characteristics of the disease. We conducted a retrospective study in 16 patients suffering from treatment-resistant MDD who underwent, during the same current episode, a cerebral perfusion SPECT with 99mTc-HM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Brain SPECT perfusions and PET metabolism appear to be discordant biomarkers in depressive disorders, as recently reported [ 28 ], with no significant relationship between brain metabolism and chronicity of illness.…”
Section: Discussionsupporting
confidence: 53%
“…Brain SPECT perfusions and PET metabolism appear to be discordant biomarkers in depressive disorders, as recently reported [ 28 ], with no significant relationship between brain metabolism and chronicity of illness.…”
Section: Discussionsupporting
confidence: 53%
“…As the ACC is considered to have a key role in the pathophysiology of the disorder, lack of normal symmetries in ACC has been long observed. In task-related fMRI, decreased functional connectivity between the left amygdala and the left ACC during negative stimuli in participants with MDD was found ( 41 ), while the increased depression duration was correlated with decreased perfusion of the right ACC ( 42 ). Consistent with the previous findings, our results suggest that lack of normal symmetries may be a characteristic for patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pattern of depression on [ 18 F] FDG PET/CT typically consists of decreased metabolic activity of the right middle frontal cortex, the right anterior cingulum cortex, the right insula, the right medial temporal cortex and the left precuneus. The duration of depression correlates with decreased activity of the right anterior cingulum cortex [32]. Additionally, a study by Tashiro et al [33] reported that the depression pattern in neurological [ 18 F]FDG PET/CT in cancer patients without brain metastasis included hypometabolic areas in limbic structures, such as the anterior and posterior cingulate gyri, the basolateral frontal cortices, as well as in the basal ganglia (especially the caudate nucleus) and frontal cortex.…”
Section: Discussionmentioning
confidence: 99%